Characterization of polyethylene wear particle: the impact of methodology - Schröder, Christian; Reinders, Jörn; Zietz, Carmen; Utzschneider, Sandra; Bader, Rainer; Kretzer, Jan Philippe (Acta biomaterialia, 2013)
Due to the prevalence of problems caused by wear particles, the reduced durability of total joint replacements is well documented. The characterization of wear debris enables the size and morphology of these wear particles to be measured and provides an assessment of the biological response in vivo. However, the impact of different methodologies of particle analysis is not yet clear. Hence, the aim of this investigation was to analyze the influence of different particle characterization methods performed by three research centers within the scope of a “round robin test”. To obtain knowledge about possible pitfalls, single steps of the particle characterization process (storage, pore size of the filter, coating durations by gold sputtering and scanning electron microscopy (SEM) magnification) were analyzed. The round robin test showed significant differences between the research groups, especially for the morphology of the particles. The SEM magnification was identified as having the greatest influence on the size and shape of the particles, followed by the storage conditions of the wear particle containing lubricant. Gold sputter coating and filter pore size also exhibit significant effects. However, even though they are statistically significant, it should be emphasized that the differences are small. In conclusion, particle characterization is a complex analytical method with a multiplicity of influencing factors. It becomes apparent that a comparison of wear particle results between different research groups is challenging.